Racial inequities in tooth loss among older Brazilian adults: A decomposition analysis. Issue 2 (13th October 2020) - Bomfim, Rafael Aiello; Schneider, Ione Jayce Ceola; de Andrade, Fabiola Bof; Lima‐Costa, Maria Fernanda; Corrêa, Vanessa Pereira; Frazão, Paulo; Watt, Richard Geddie; Bastos, João Luiz; de Oliveira, Cesar
Abstract: Objective: To determine the extent to which racial inequities in tooth loss and functional dentition are explained by individual socioeconomic status, smoking status and frequency/reason for the use of dental services. Methods: Data came from the Brazilian Longitudinal Study of Ageing, a nationally representative sample of community‐dwelling people aged 50 years and over. Tooth loss and functional dentition (ie 20+ natural teeth) were the outcomes. The main explanatory variable was self‐classified race. Covariates included dental visits in the past 12 months, dental visits for check‐ups only, smoking status, self‐reported chronic conditions, depression and cognitive function. Logistic regression and Blinder‐Oaxaca decomposition analysis were used to estimate the share of each factor in race‐related tooth loss inequities. Results: The analytical sample comprised of 7126 respondents. While the prevalence of functional dentition in White Brazilians was 37% (95% CI: 33.5;40.9), it was 29% (95% CI: 26.4;31.6) among Browns and 30% (95% CI: 25.1;35.4) among Blacks. The average number of lost teeth among Whites, Browns and Blacks were 18.7 (95% CI: 17.8;19.6), 20.4 (95% CI: 19.7;21.1) and 20.8 (95% CI: 19.5;22.0), respectively. Decomposition analysis showed that the selected covariates explained 71% of the racial inequalities in tooth loss. Dental visits in the previous year and smoking status explained nearly half of race‐related gaps. Other factors, such as per capita income, education and cognitive status, also had an important contribution to the examined inequalities. The proportion of racial inequities in tooth loss that was explained by dental visits (frequency and reason) and smoking status decreased from 40% for those 50‐59 years of age to 22% among participants aged 70‐79 years. Conclusions: Frequency and reason for dental visits and smoking status explained nearly half of the racial inequity in tooth loss among Brazilian older adults. The Brazilian Family Health Strategy Program should target older adults from racial groups living in deprived areas.